Pengaruh Iklim Sekolah Terhadap Hasil Belajar Siswa - Fazar Nuriansyah; Kinanti Geminastiti Hilmiatussadiah; Luthfi Rahman Hidayat (Universitas Negeri Padang, 2023)
The irregular and downward trends in student learning results serve as the driving force for this study. The objective of this study is to determine how school climate impacts student learning results. A questionnaire is used in the data gathering process, which is a survey method. To test the hypothesis, determine the R2 coefficient of determination and do a partial test (t test). The findings indicated that student learning outcomes were positively impacted by school atmosphere. According to study findings, it is essential to maximize the responsibilities played by students, teachers, schools, and the government in order to foster a positive school climate that influences learning outcomes.